2020
DOI: 10.1002/cmdc.201900662
|View full text |Cite
|
Sign up to set email alerts
|

Further Investigations into Rigidity‐Activity Relationships in BisQAC Amphiphilic Antiseptics

Abstract: Thirty‐six biscationic quaternary ammonium compounds were efficiently synthesized in one step to examine the effect of molecular geometry of two‐carbon linkers on antimicrobial activity. The synthesized compounds showed strong antimicrobial activity against a panel of both Gram‐positive and Gram‐negative bacteria, including methicillin‐resistant Staphylococcus aureus (MRSA). While the linker geometry showed only a modest correlation with antimicrobial activity, several of the synthesized bisQACs are promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Commercial QAC formulations are often dilute solutions (generally between 0.01% and 1%) and may contain a combination of multiple QACs. Recently, investigations into the structure-activity relationships of simple QAC scaffolds have revealed that incorporation of multiple ammonium cations and decreasing structural rigidity of QACs may lead to improved efficacy and therapeutic indices (Leitgeb et al, 2020).…”
Section: Quaternary Ammonium Compound Resistancementioning
confidence: 99%
“…Commercial QAC formulations are often dilute solutions (generally between 0.01% and 1%) and may contain a combination of multiple QACs. Recently, investigations into the structure-activity relationships of simple QAC scaffolds have revealed that incorporation of multiple ammonium cations and decreasing structural rigidity of QACs may lead to improved efficacy and therapeutic indices (Leitgeb et al, 2020).…”
Section: Quaternary Ammonium Compound Resistancementioning
confidence: 99%
“…Our reports from 2019 and 2020 documented variations in bisQAC rigidity through the addition of linking methylene groups (Figure 1A) and pi-bond modification (Figure 1B), respectively. [21][22] Each of these investigations led to the elucidation of highly potent antimicrobials, although the more rigid TMEDA-based structures in Figure 1A [21] showed superior activity, while the more flexible alkane-linked bispyridinium compounds in Figure 1B [22] were more active than their unsaturated counterparts. We posited that cation proximity might play a role in this pair of observations.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the connection of two pyridinium units (bis-pyridinium QACs, Figure 1a), usually with long-chain alkyl substitution, largely increases the antibacterial efficiency, and several studies have shown that antibacterial activity is influenced by linker rigidity, spacing, and relative orientation of the introduced charges. 5,7 Singlet oxygen is a highly toxic ephemeral species that is widely used in photodynamic therapy. 10−12 It is usually produced from irradiation of photosensitizers in the presence of triplet oxygen.…”
mentioning
confidence: 99%
“…New tunable lead structures for broad spectrum antibiotics are highly sought after due to the emergence of multidrug resistant bacteria. Of particular concern are mycobacteria, such as Mycobacterium tuberculosis , but also other opportunistic pathogens like Staphylococcus aureus . An important class of efficient antibacterial compounds includes the quaternary ammonium compounds (QACs), and a wide range of QAC derivatives have been prepared. These compounds usually target the bacterial membrane. Importantly, the connection of two pyridinium units (bis-pyridinium QACs, Figure a), usually with long-chain alkyl substitution, largely increases the antibacterial efficiency, and several studies have shown that antibacterial activity is influenced by linker rigidity, spacing, and relative orientation of the introduced charges. , …”
mentioning
confidence: 99%
See 1 more Smart Citation